COFFEE LAND COVER CHANGES ANALYSES: A STUDY CASE IN SÃO PAULO STATE - Coltri, Priscila Pereira; Lima, Paulo Renato; Koga-Vicente, Andrea; Gonçalves, Renata Ribeiro do Valle (Coffee Science - ISSN 1984-3909, 2019)
In this research, we combine data analyses with hotspots method to identify the spatio-temporal trend of São Paulo’s coffee cultivation area. Our hypothesis is that coffee cultivation area has been changing significantly in the study area since 1990. Therefore, the main goal of this research was to map the spatial pattern of coffee land use change. For coffee land use diagnostics, official data of cultivated area, hotspot analyses and growth rate were used. The results demonstrated that coffee cultivation area decreased and concentrated in smaller areas, which are traditionally recognized as “coffee quality regions”. The producer size analyses evidenced that, not only the localization, but also the producer profile changes as well. Smallholders increased but medium and large producers decreased significantly in the studied period. The coffee abandonment analyses demonstrated that, over the study period, 51.46% of the coffee area cultivated in the study region was abandoned.